Genomics, proteomics, and metabolomics in nutraceuticals and functional foods - Bagchi, Manashi; Lau, Francis [ (Francis C.)] (Wiley-Blackwell, 2010)
"The nutraceutical and functional food field is rapidly growing in diverse sectors, including academic, commercial and government. This has brought a corresponding shift in research focus and in public awareness. Understanding the relevance of the scientific principles in determining the safety and effectiveness of functional foods and nutraceuticals is increasingly important. It is becoming increasingly evident that genomic research technologies will be increasingly used in the coming years and there is a need to provide resources that will facilitate this growth. This book incorporates the most recent advances in the three major sectors of the field within one volume. Genomics, proteomics, and metobolomics represent three major scientific research areas that contribute to nutraceutical and functional food research for studies of effectiveness and safety"--Provided by publisher